Menyeimbangkan Ritualitas dan Partisipasi Sosial: Konsep Tasawuf Sosial Amin Syukur - Randi Saputra; Reza Pahlevi Dalimunthe; Mulyana Mulyana (IAIN Palangka Raya, 2021)
This study was aimed at analyzing the concept of social Sufism of Amin Syukur. This study used a qualitative approach by placing the researcher as the key instrument, and was combined with a biographical study of thoughts. Literature study was chosen as a data collection technique by exploring various relevant sources. The finding revealed that in the concept of social Sufism ofAmin Syukur, becoming a Sufi did not have to be part of a particular tarekat school. In addition, the paradigm promoted in social Sufism was that Sufism was not a passive and individualist teaching. This paradigm was motivated by Amin Syukur's thought that humans were social beings having roles and functions in social life. At this level a Sufi was placed as an agent of change and social control. Therefore, in Amin Syukur's view, Sufism was not only related to ritualit, which gave birth to individual piety, but also had implications for participation in social, cultural, and political life, which gave birth to social piety. Thus, it was concluded that social Sufism was a moderate concept emphasizing the balance between individual and social pious. The concept of social Sufism allowed humans to become Sufis without having to join a particular tarekat group first.Keywords: Social Sufism; Amin Syukur; Individual Pious; Social Pious